PROBLEMS AND PROSPECTS OF DEVELOPMENT OF URBAN ELECTRIC TRANSPORT - Hnedin, K. V. (Science and Transport Progress, 2007)
General tendencies, actual problems and perspective trends of the development of enterprises of city electric transport are determined in the article. The complex of arrangements directed to stabilization of the work of the enterprises of the field is proposed.